Atlas of the Islamic world since 1500 - Robinson, Francis (New York : Facts On File, 1982)
Explores the geographical/ethnographic background, and cultural history of the Islamic world, and features a tour of modern-day regions. Includes a chronological table, over fifty maps, and illustrations.
Map on endpapers.
Includes bibliographical references (p. 229-231) and index.
Booklist.
Choice.
Library Journal.
Young Ad.-Adult.
Keywords: Atlases; Atlases; Islamic countries -- Maps; Islamic countries -- Antiquities; Islamic countries -- Civilization; Islamic countries -- History; Islamic countries -- Maps; Islamic countries -- Antiquities; Islamic countries -- Civilization; Islamic countries -- History